DEVELOPMENT OF PBL-BASED INTERACTIVE E-MODULES TO IMPROVE CRITICAL THINKING SKILLS OF GRADE 4 STUDENTS IN MATHEMATICS AT SDN 060866 MEDAN - Try Rahayu; Albert Pauli Sirait; Wildansyah Lubis; Elvi Mailani; Apiek Gandamana (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2026)
This research is motivated by the low critical thinking skills and learning outcomes of students in mathematics subjects in grade IV of SDN 060866 Medan, which is caused by learning that is still centered on the teacher and the unavailability of interactive learning media that supports the learning process. This study aims to determine the feasibility, practicality, and effectiveness of developing interactive e-modules based on Problem Based Learning (PBL) to improve critical thinking skills of grade IV students in mathematics subjects. The type of research used is Research and Development (R&D) with the ADDIE development model which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects were a material expert, a question expert, a design expert, teachers and grade IV students of SDN 060866 Medan, totaling 23 students. Data collection instruments included validation sheets of material experts, question experts, design experts, teacher practicality questionnaires, as well as pre-test and post-test tests to measure effectiveness. The research results showed that the developed e-module was deemed highly feasible, with validation results from material experts reaching 87.69%, validation from question experts reaching 84.61%, and validation from design experts reaching 95.65%. The practicality test yielded a score of 98.6%, categorized as very practical. Furthermore, the e-module also proved highly effective, with a student learning completion rate of 91% and an average score increase from 53.75 in the pre-test to 87.75 in the post-test, representing a 34-point increase. Therefore, the developed interactive e-module based on Problem-Based Learning was deemed feasible, practical, and effective for use in mathematics learning to improve the critical thinking skills of fourth-grade students at SDN 060866 Medan.